INVESTIGASI ZONA AKUIFER MENGGUNAKAN METODE GEOLISTRIK KONFIGURASI SCHLUMBERGER DI PANTAI PARANGLUHU KECAMATAN BONTOBAHARI, KABUPATEN BULUKUMBA - Wahyuni Wahyuni; Jamaluddin Jamaluddin; Sabrianto Aswad; La Ode Armin (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2018)
Water is a natural resource that is essential for needs of living things, especially human beings. Most groundwater widely utilized because the standards compliance of clean water and proper use. However there is a difference in the conditions and quality of the groundwater in different areas, one of which on the territory of coastal zone that can store brackish ground water – salty. This is a lot going on in various parts of the territory of one of the coastal zone subdistrict of Bontobahari. Related conditions, this research was conducted with the aim to find out the characteristics of the aquifer and the salty soil water distribution in the region of coastal zone subdistrict of Bontobahari, Bulukumba. The methods used in this research is the geoelectric resistivity injection using the Schlumberger configuration. Based on the measurement and data processing, resisvity values of aquifer have about 29,4 – 36,1 Ωm and it can be found at a depth of 6,50 – 19,7 m.